2020
DOI: 10.1111/jonm.13066
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of applying for hospital accreditation: The perspective of staff

Abstract: Aim This investigation aimed to explore the benefits associated with implementing an accreditation programme in hospitals in Jordan, from the perspective of doctors and nursing staff. Background Although Jordan is one of the first Arab countries in the Middle East to adopt accreditation standards, little has been identified with regard to the benefits of implementing accreditation for the quality of health care in Jordanian hospitals. Method A qualitative approach was employed in this project. Face‐to‐face int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 26 publications
3
17
0
Order By: Relevance
“…The participants reported that the healthcare accreditation resulted in several benefits to patient safety and quality of healthcare in their organizations. These positive views regarding accreditation are consistent with previous studies in which HCPs supported accreditation programs and believed that accreditation resulted in improvements within their organizations 10,12,15,20,24,28,38 . For example, a survey‐based study from Qatar showed that most staff working in a primary healthcare organization agreed about the positive impact of accreditation on quality of healthcare 15 .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The participants reported that the healthcare accreditation resulted in several benefits to patient safety and quality of healthcare in their organizations. These positive views regarding accreditation are consistent with previous studies in which HCPs supported accreditation programs and believed that accreditation resulted in improvements within their organizations 10,12,15,20,24,28,38 . For example, a survey‐based study from Qatar showed that most staff working in a primary healthcare organization agreed about the positive impact of accreditation on quality of healthcare 15 .…”
Section: Discussionsupporting
confidence: 85%
“…In a similar study from Saudi Arabia, HCPs perceived accreditation to result in positive improvements in the delivery of patient care and other health services at their hospital 20 . In a qualitative study conducted among hospital physicians and nurses in Jordan, participants expressed favourable attitudes towards accreditation and reported several benefits of accreditation including quality improvement, patient safety and satisfaction, cost‐effectiveness, and enhanced reputation 28 . In a nationwide survey in Australia on the benefits of a national accreditation program, most HCPs indicated that accreditation resulted in significant benefits to healthcare organizations 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these 20 publications, 15 indicated that accreditation programmes positively affect organisational performance (AbuAlRub et al, 2015;Al Shammari et al, 2015 Impact of hospital accreditation Al-Qahtani et al, 2012;Algahtani et al, 2017;Algunmeeyn et al, 2020;Almasabi and Thomas, 2017;Bahadori et al, 2018;Diab, 2011;Jaafaripooyan, 2014;Jaber, 2014;Reisi et al, 2019;Saadati et al, 2018;Shakibaei, 2019;Yousefinezhadi et al, 2020). For instance, hospital accreditation was perceived to promote a quality and safety culture by improving communication, teamwork and staff empowerment, and enhancing clinical documentation (AbuAlRub et al, 2015;Al Shammari et al, 2015;Al-Awa et al, 2012;Algunmeeyn et al, 2020;Saadati et al, 2018;Yousefinezhadi et al, 2020).…”
Section: Organisational Impactsmentioning
confidence: 99%
“…Of these 20 publications, 15 indicated that accreditation programmes positively affect organisational performance (AbuAlRub et al, 2015;Al Shammari et al, 2015 Impact of hospital accreditation Al-Qahtani et al, 2012;Algahtani et al, 2017;Algunmeeyn et al, 2020;Almasabi and Thomas, 2017;Bahadori et al, 2018;Diab, 2011;Jaafaripooyan, 2014;Jaber, 2014;Reisi et al, 2019;Saadati et al, 2018;Shakibaei, 2019;Yousefinezhadi et al, 2020). For instance, hospital accreditation was perceived to promote a quality and safety culture by improving communication, teamwork and staff empowerment, and enhancing clinical documentation (AbuAlRub et al, 2015;Al Shammari et al, 2015;Al-Awa et al, 2012;Algunmeeyn et al, 2020;Saadati et al, 2018;Yousefinezhadi et al, 2020). Health professionals also viewed hospital accreditation programmes as effective interventions to improve and standardise care processes, stimulate organisational changes and improve managerial processes (Al-Qahtani et al, 2012;Algahtani et al, 2017;Almasabi and Thomas, 2017;Bahadori et al, 2018;Diab, 2011;Jaafaripooyan, 2014;Jaber, 2014;Reisi et al, 2019;Saadati et al, 2018;Shakibaei, 2019).…”
Section: Organisational Impactsmentioning
confidence: 99%